Global Governance and Regulatory Failure - Goldbach, R. author. aut Link
XIV, 271 p.
Keywords: The author provides a theoretical framework of the global political economy of banking regulation and analyses the policies and politics of the Basel Committee on Banking Supervision. He demonstrates how global governance has contributed to the onset of the Great Recession and continues to increase the likelihood of future global financial crises.